Where do we go now since 2002? A bibliometric analysis of augmented reality-related studies in education and training - Arifin, Muhammad Aiman; Razali, Razlina; Kamal, Ummu Athilia (Journal of Islamic, Social, Economics and Development, 2025)
Augmented reality (AR) has emerged as a transformative technology in education and training, demonstrating significant potential to enhance learner performance. Since 2002, it has garnered substantial academic interest and expanded publication opportunities. However, a comprehensive review of AR-related research in educational contexts has yet to be conducted. To address this gap, the current study employs VOS Viewer and Bibliometrix R-package software to perform a bibliometric analysis of the scientific literature concerning AR in education and training. This analysis focuses on several key aspects: (1) prominent authors and countries; (2) productive journals; (3) most cited articles; (4) co-authorship among countries; (5) trending topics; (6) thematic map and; (7) co-occurrence analysis of keywords. The researchers sourced publications from the Scopus database from 2002 onward, revealing that AR remains an active study area with a growing body of literature dedicated to its application in education and training. This bibliometric review aims to guide future research directions by offering a thorough overview of the current landscape of AR in education and training settings.